Altered Brain Adiponectin Receptor Expression in the 5XFAD Mouse Model of Alzheimer's Disease - Anishchal A. Pratap; R. M. Damian Holsinger (MDPI AG, 2020)
Metabolic syndromes share common pathologies with Alzheimer's disease (AD). Adiponectin, an adipocyte-derived protein, regulates energy metabolism via its receptors, AdipoR1 and AdipoR2. To investigate the distribution of adiponectin receptors (AdipoRs) in Alzheimer's, we examined their expression in the aged 5XFAD mouse model of AD. In age-matched wild-type mice, we observed neuronal expression of both ARs throughout the brain as well as endothelial expression of AdipoR1. The pattern of receptor expression in the aged 5XFAD brain was significantly perturbed. Here, we observed decreased neuronal expression of both ARs and decreased endothelial expression of AdipoR1, but robust expression of AdipoR2 in activated astrocytes. We also observed AdipoR2-expressing astrocytes in the dorsomedial hypothalamic and thalamic mediodorsal nuclei, suggesting the possibility that astrocytes utilise AdipoR2 signalling to fuel their activated state in the AD brain. These findings provide further evidence of a metabolic disturbance and demonstrate a potential shift in energy utilisation in the AD brain, supporting imaging studies performed in AD patients.